Biomechanical analysis of table tennis moving - Wang, J.; Baikai, X.; Cheng, X. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Table tennis is a fast action sport and success requires highly skilled players that are capable of hitting and anticipating the fast movement of the ball under different circumstances. In this respect, the analysis of the table tennis ball forces and motion, such as spin and flight line and change of rebound speed and angle under different conditions is very important for understanding the game and helping athletes to strengthen their judgment ability of anticipating the ball`s motion and improving their game through the scientific guidance of training. Methods The movement of the table tennis ball is determined by the external forces exerted on it, which mainly include the driving force from the bat and the frictional force with it, gravity and the pressure from air currents. None of them can be neglected since the table tennis ball is light and small. The reasons which lead to the complication of the movement of the table tennis ball in the air are analysed in the following section. Spin of a table tennis ball is divided into topspin, under spin, sidespin and composite spin. The table tennis ball rotates in the air around its own centre. This will cause changes of its flying lines and there are changes of reflecting speed and angle when it hits the opposite side of the table. Therefore, to improve a player`s game it is important to understand the rules of table tennis ball movement by starting from understanding the spin of table tennis ball first. The table tennis ball spin speed and spin direction were analysed from two aspects: a) determining the table tennis ball spin speed and spin angle through tracing special colour marks on the ball by means of high-speed videotaping and image analysis; b) determining the table tennis ball spin speed and spin angle through analysing the stress of the table tennis ball. This was performed using an Ariel (Ariel, USA) high-speed three-dimensional video analysis system. The table tennis ball was coated with three pigments of red, yellow and white colours. In order to identify the three colours on the table tennis ball more accurately on the images, the lights in the table tennis hall (experimental area) must be very bright. Therefore, all the lights in the hall were switched on and additional iodine-tungsten lamps were used at the four corners. The movements were videotaped by positioning the high-speed camera at the side of the table. The sampling frequency was 300 frames/s in order to capture adequately the topspin and underspin of the ball. Conclusions 1. The movement of the table tennis ball is determined by the external forces exerted on it and the parabolic motion is decided by the driving force from the bat and gravity and the pressure from air-current; the spin motion is decided by the frictional force from the bat with it. 2. The spin of table tennis ball includes topspin, underspin, sidespin and composite spin. Each type of spin is affected by the frictional force in the opposite direction. 3. The flight line of the table tennis ball is determined by the degree, angle and direction of the acting force imposed by the bat on the ball. 4. The rebound speed and angle of the ball after table impact changes and the high-level players always deal with their reception in a highly skilled manner to make the rebound speed and angle of the ball change irregularly.